Zeb1 promotes androgen independence of prostate cancer via induction of stem cell-like properties. (July 2014) - Li, Ping; Wang, Jia; Chu, Mingliang; Zhang, Kaiqing; Yang, Ru; Gao, Wei-Qiang
Current androgen deprivation therapy often leads to androgen independence. However, mechanism of the therapeutic failure is still not well understood. Here, we demonstrate elevated expression of Zeb1 in androgen-independent prostate cancer cells and prostate tumors of castrated PTEN conditional knockout mice. While Zeb1 shRNA resulted in a sensitization of androgen-independent prostate cancer cells, forced Zeb1 expression caused androgen-dependent prostate cancer cells to be more resistant to androgen deprivation. Moreover, such effects appeared to be mediated by induction of pluripotent genes or stem cell-like properties. Collectively, these findings suggest that inhibition of Zeb1 might be a potential therapeutic strategy for treatment of androgen-independent prostate cancer.